Infant emmetropization: longitudinal changes in refraction components from nine to twenty months of age. - Ehrlich, D; Braddick, O; Atkinson, J; Anker, S; Weeks, F; Hartley, T; Wade, J; Rudenski, A (1997)
Rapid emmetropization is described in pediatrically normal infants from 9 months of age during the following year. The infants, obtained from various categories of the Cambridge population screening program, provided a broad range of refractive errors. The large group of 254 nonanisometropic infants studied allowed the mean rate of change and dependence on the initial refraction value to be determined. Refraction was measured by cycloplegic retinoscopy. Rapid emmetropization changes occurred in the following refractive components: mean spherical equivalent (MSE), astigmatism magnitude, the horizontal astigmatism component, the infant's most positive meridian, and the infant's most negative meridian. The MSE and astigmatism rates of change (diopters/year), were highly dependent on their respective initial powers (r = -0.61 and r = -0.76). The percentage weighted mean proportional rate of change for MSE was -30% (SE 4%) and for astigmatism magnitude it was -59% (SE 14%). There was much individual variation, with some exhibiting fast emmetropization and others not. The MSE and astigmatism changes, however, were almost independent of each other. The refractive errors of the most positive and most negative meridians emmetropize because they are both derived from the MSE and half the astigmatism. With-the-rule astigmatism was more prevalent than against-the-rule astigmatism at 9 months of age, and with-the-rule astigmatism exhibited a significantly greater proportional rate of change. The relationship of emmetropization and refractive screening is considered. A new component "MOMS" is introduced, the maximum ocular meridional separation, when both eyes are considered. Thus incorporating astigmatism and anisometropia may be a good single indicator of conditions associated with later amblyopia. The almost independent emmetropization of the MSE and astigmatism components is an important result to consider in theories of emmetropization, refractive screening, clinical prescribing, and the evaluation of infants in treatment trials.